The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1164/rccm.201309-1611oc
|View full text |Cite
|
Sign up to set email alerts
|

Presence of B Cells in Tertiary Lymphoid Structures Is Associated with a Protective Immunity in Patients with Lung Cancer

Abstract: Rationale: It is now well established that immune responses can take place outside of primary and secondary lymphoid organs. We previously described the presence of tertiary lymphoid structures (TLS) in patients with non-small cell lung cancer (NSCLC) characterized by clusters of mature dendritic cells (DCs) and T cells surrounded by B-cell follicles. We demonstrated that the density of these mature DCs was associated with favorable clinical outcome. Objectives: To study the role of follicular B cells in TLS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
616
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 619 publications
(697 citation statements)
references
References 48 publications
(56 reference statements)
34
616
3
7
Order By: Relevance
“…In lung tumour‐associated ELFs, a high proportion of mature DCs correlate with gene signatures linked with Th1 cell activation and improved long‐term patient survival 97. Similar observations have been reported for B‐cell densities in NSCLC, where follicular B cells correlate with long‐term survival both in early‐stage disease and in advanced disease treated with chemotherapy 96. Therefore, ELF development may facilitate the recruitment of naive T and B cells from the peripheral pool via HEVs and homeostatic chemokines.…”
Section: Elfs As Regulators Of Anti‐tumour Immunitymentioning
confidence: 54%
See 1 more Smart Citation
“…In lung tumour‐associated ELFs, a high proportion of mature DCs correlate with gene signatures linked with Th1 cell activation and improved long‐term patient survival 97. Similar observations have been reported for B‐cell densities in NSCLC, where follicular B cells correlate with long‐term survival both in early‐stage disease and in advanced disease treated with chemotherapy 96. Therefore, ELF development may facilitate the recruitment of naive T and B cells from the peripheral pool via HEVs and homeostatic chemokines.…”
Section: Elfs As Regulators Of Anti‐tumour Immunitymentioning
confidence: 54%
“…In this context, it is therefore surprising that ELFs arise in tumours at all. However, ELFs have been described in numerous cancers including colorectal,60, 88 rectal,89 breast,67, 90, 91 ovarian67, 92 and germ cell93 cancers, as well as melanoma,62, 67, 94 mucosal‐associated lymphoid tissue lymphoma39 and non‐small cell lung carcinoma95, 96 (NSCLC; see Dieu‐Nosjean et al . for a comprehensive review of ELFs in cancer9).…”
Section: Elfs As Regulators Of Anti‐tumour Immunitymentioning
confidence: 99%
“…Tertiary lymphoid structures (TLSs; also called ectopic lymphoid structures, ELSs) are inducible lymphoid aggregates that phenotypically and functionally resemble secondary lymphoid organs 4. TLSs can develop in tissues where persistent inflammation is present, and a correlation between high TLS densities and prolonged patient survival has been reported for several cancers including breast,5, 6 lung,7, 8 melanoma,9 pancreatic10 and colorectal 11, 12. TLS gene signatures, that include homeostatic chemokines such as CXCL13 , CCL19 and CCL21 , have the potential to represent prognostic indicators of cancer progression in melanoma13 and colorectal cancer 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…For example, clonal expansion of interferon‐(IFN)‐γ producing T cells reactive to tumour antigens, which inhibit tumour growth, have been observed in experimental mouse melanoma 16, 17. Improved patient survival in non‐small‐cell lung carcinoma has also been linked with TLSs, where follicular B cells and plasma cells show antibody specificity to tumour antigens 8. However, TLS involvement and activity may only have prognostic value in certain stages of tumour development or for certain types of cancer 11, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Mechanistically, this antitumour effect is associated with the activation of B cell maturation machinery and presence of tumour antigen-specific antibodies. 6 Despite the well-characterized role of infiltrating B cells and TLOs, the role of Tfh in human lung cancers remains understudied. 7 Infection models have revealed that circulating Tfh function differently from those in lymphoid tissue and correlate with opposing outcomes.…”
Section: Introductionmentioning
confidence: 99%